"No evident disease activity": The use of combined assessments in the management of patients with multiple sclerosis. (August 2017) - Giovannoni, Gavin; Tomic, Davorka; Bright, Jeremy R; Havrdová, Eva
Using combined endpoints to define no evident disease activity (NEDA) is becoming increasingly common when setting targets for treatment outcomes in multiple sclerosis (MS). Historically, NEDA has taken account of the occurrence of relapses, brain magnetic resonance imaging (MRI) lesions and disability worsening, but this approach places emphasis on inflammatory activity in the brain and mostly overlooks ongoing neurodegenerative damage. Combined assessments of NEDA which take account of changes in brain volume or neuropsychological outcomes such as cognitive function may begin to address this imbalance, and such assessments may also consider blood or spinal-fluid neurofilament levels or patient-reported outcomes and quality of life measures. If a combined NEDA assessment can be validated in prospective studies as indicative of long-term disease remission at the individual patient level, treating to achieve NEDA could become the goal of clinical practice and achieving NEDA may become the "new normal" state of disease control for patients with MS.